Islam, the tool : tolerating racial and religious discrimination in Singapore. - Nur Rashidah Amren. (2011)
Meritocracy means every Singaporean has equal chance of success regardless of race, language or religion. However, the government's approach to ethnicity and multiculturalism undermines the work of meritocracy. Dividing Singaporeans according to race means there is bound to have one group favoured over the others. Where do Malay Muslims stand in Singapore? What kind of problems do they face living in Singapore as a minority? Where are their voices? This paper seeks to examine whether increasing religiosity among Malay Muslims results in the increase of tolerance to racial and religious discrimination in Singapore.